A Simple and Efficient Synthesis of Fused Benzo[b]thiophene Derivatives - Ulyankin, Evgeny B.; Kostyuchenko, Anastasia S.; Chernenko, Sergey A.; Bystrushkin, Mikhail O.; Samsonenko, Anna L.; Shatsauskas, Anton L.; Fisyuk, Alexander S. (Synthesis, 2021)
A new approach to the synthesis of fused benzothiophene derivatives was developed based on iodine-promoted photocyclization of 4,5-diaryl-substituted thiophenes obtained in three steps from commercially available compounds. Comparative analysis showed that photochemical cyclization is a more efficient method for the preparation of fused benzo[b]thiophene derivatives, compared to oxidative coupling of 4,5-diaryl-substituted thiophenes in the presence of iron(III) chloride and palladium-catalyzed intramolecular arylation. This new approach provides an efficient synthesis of functionally substituted naphtho[2,1-b:3,4-b′]dithiophenes, phenanthro[9,10-b]thiophenes, benzo[1,2-b:3,4-b′:6,5-b′′]trithiophenes, as well as new fused heterocycles containing a pyridine ring and/or a carbazole moiety.
Keywords: heterocycles; fused-ring systems; photochemistry; cyclization; molecular electronics